RELIGIOUS COURT COMPETENCE IN SHARIA ECONOMIC DISPUTE COMPLETION - Dhaifina Fitriani (Universitas Islam Negeri Mataram, 2020)
Sharia economic problems are problems that are still new and not well known in the legal world. The competence of the Religious Courts in sharia economic matters is mentioned in Law Number 21 of 2008 concerning Sharia Banking which provides competence to the Religious Courts in handling sharia economic matters (disputes). The authority of the Religious Courts in Law No. 3/2006 confirms that